Figurative Calligraphy: Artistic, Magic, and Religious Aspect of the Cirebon Glass Painting - Agung Zainal Muttakin Raden; Mohamad Sjafei Andrijanto; Wirawan Sukarwo (Universitas Indraprasta PGRI, 2019)
Cirebon glass painting is a particularly famous artwork related to Islamic art in Indonesia. Aside from its aesthetic values, Cirebon glass painting also contained the symbol and message behind its ornaments. Figurative calligraphy with Arabic script is frequently used by glass painting artisans to make Cirebon glass painting. The resulted figurative calligraphy can take form resembling those of human figure, plants, animals, wayang, and the imaginary entity or particular symbols. As it is, Cirebon is one of the busiest port city in Java island. Therefore, many cultural exchanges happened by the interaction of many nationalities visiting Cirebon which later on assimilated to the local culture. This makes Cirebon glass painting unique since it was influenced by a mixture of cultures. This research focused on the elements that are contained on the Cirebon glass painting based on the artistic, magic, and religious aspect. The result in this research has an implication to expose the symbols, message and meaning behindCirebon glass painting and its synergy with the artistic, magic, and religious aspect that makes Cirebon glass painting survived and still doing well in Cirebon society nowadays.